Cash transfers conditional on schooling reduce IPV among young women in South Africa - Cash Transfer and Intimate Partner Violence Research Collaborative; University of North Carolina Gillings School of Global Public Health (International Food Policy Research Institute, 2019)
This case study summarizes the impact from a conditional cash transfer program targeted to girls of secondary school age in South Africa. The program led to a 34 percent reduction in intimate partner physical violence by allowing girls to avoid potential violent partnerships, as transfers delayed sexual debut and lowered their number of sexual partners.